2019
DOI: 10.1002/rcm.8548
|View full text |Cite
|
Sign up to set email alerts
|

Identification of carbonylated proteins in a bactericidal process induced by curcumin with blue light irradiation on imipenem‐resistant Acinetobacter baumannii

Abstract: Rationale Antimicrobial photodynamic treatment is potentially an alternative to antibiotics and is also effective against viruses, fungi and some cancers. Our previous studies have shown that blue light combined with curcumin, a chemical from the turmeric plant, exerted effective antimicrobial activity via photodynamic treatment. The study reported in this paper investigates which target proteins are affected after the treatment. Methods We treated imipenem‐resistant Acinetobacter baumannii with blue light and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The A. baumannii inactivation efficiency shown for RF-aPDT in our study, is similar to that reported for Aloe emodin, although the former was achieved applying a ten-times higher dye concentration and a twice-higher illumination dose. Chang et al [ 26 ] reported 97.5% inhibition of imipenem-resistant A. baumannii planktonic cells with curcumin-based aPDT. The effect was achieved by applying a 0.2 mM PS concentration and blue light irradiation using a 5.4 J/cm 2 illumination dose (3 mW/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A. baumannii inactivation efficiency shown for RF-aPDT in our study, is similar to that reported for Aloe emodin, although the former was achieved applying a ten-times higher dye concentration and a twice-higher illumination dose. Chang et al [ 26 ] reported 97.5% inhibition of imipenem-resistant A. baumannii planktonic cells with curcumin-based aPDT. The effect was achieved by applying a 0.2 mM PS concentration and blue light irradiation using a 5.4 J/cm 2 illumination dose (3 mW/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, data on natural PS-based aPDT perspectives in the control of emerging multidrug resistant hospital infection agents and their biofilms remain scarce. For A. baumannii aPDT inactivation, only a few natural PSs [ 25 , 26 , 27 , 28 ] have been analyzed, although none of these studies addressed biofilm inactivation. Furthermore, no research has been performed on S. maltophilia aPDT inactivation, neither with natural nor with other PSs.…”
Section: Introductionmentioning
confidence: 99%
“…in food-related diseases, periodontitis, wound healing, and multidrug resistance. Curcumin concentrations ranging from 0.5 µM to 6.1 mM have been effectively used in APDT studies [ 35 , 77 , 78 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. In addition, mosquito larvae are controlled by curcumin exposure for 120 min at a light intensity of 220 W/m 2 [ 91 ].…”
Section: Natural Pss In Apdtmentioning
confidence: 99%
“…The antimicrobial activity of riboflavin under illumination has been demonstrated against a variety of microorganisms (Table 3). Acinetobacter baumannii [211] Aggregatibacter actinomycetemcomitans [212,213] Escherichia coli [214][215][216][217][218][219][220] Enterococcus faecalis [221][222][223][224][225][226][227] Helicobacter pylori [228] Lactobacillus casei [179] Listeria innocua [216,229] Listeria monocytogenes [230,231] Porphyromonas gingivalis [212] Propionibacterium acnes [224,232] Pseudomonas [233] Pseudomonas aeruginosa [234] Staphylococcus aureus [177,214,215,218,220,[234][235][236][237][238][239][240][241][242][243] Salmonella strains [230] Salmonella typhimurium…”
Section: Riboflavinmentioning
confidence: 99%